Assessing the Impact of Small-Scale Firms on Household Welfare in Uganda: A Case Study of Muhanga Town Council in Rukiga District. - Kukundakwe, Danise (Kabale University, 2023)
The industrial sector in Uganda is characterized by small-scale and large-scale manufacturing and processing small-scale firms where fewer often are foreign-owned. However, in Uganda, despite small-scale firms being a key vehicle for economic success, having the potential to provide employment opportunities to the millions of unemployed people and having the capacity to contribute to Gross Domestic Product (GDP) as well as poverty reduction to improve on household welfare, still the house bold welfare people have not been realized. It has been revealed that three out of five small-scale firms in Uganda fail within the first two years of operation and those that continue 80 percent fail before the fifth year. Small-scale firms including those of MMuhanga town council in Rkiga district have issues like inadequate skills among the business operators, inadequate capital, and high taxes, which affect their success and profitability and hinder their ability to contribute effectively to the sustainable growth and development of the businesses and improvement of household welfare. This situation prompted the researcher to carry out a study on the impact of small-scale firms on household welfare in Uganda a case study of Muhanga Town Council in Rukiga district. The purpose of the study was to assess the impact of small-scale firms on household we! fare in Uganda a case study of Muhanga Town Council in Rukiga district.